Prevalence and outcomes of atrial fibrillation in patients suffering prostate cancer: a national analysis in the United States - Pan, Zhemin; Xu, Xiao; Xu, Xi; Wu, Shengyong; Zhang, Zhensheng; Liu, Suxuan; Liu, Zhijian; Tu, Boxiang; Chen, Chenxin; Qin, Yingyi; He, Jia (Frontiers in Cardiovascular Medicine, 2024)
Purpose: Although the adverse effects of atrial fibrillation (AF) on cancers have been well reported, the relationship between the AF and the adverse outcomes in prostate cancer (PC) remains inconclusive. This study aimed to explore the prevalence of AF and evaluate the relationship between AF and clinical outcomes in PC patients. Methods: Patients diagnosed with PC between 2008 and 2017 were identified from the National Inpatient Sample database. The trends in AF prevalence were compared among PC patients and their subgroups. Multivariable regression models were used to assess the associations between AF and in-hospital mortality, length of hospital stay, total cost, and other clinical outcomes. Results: 256,239 PC hospitalizations were identified; 41,356 (83.8%) had no AF and 214,883 (16.2%) had AF. AF prevalence increased from 14.0% in 2008 to 20.1% in 2017 (P < .001). Inhospital mortality in PC inpatients with AF increased from 5.1% in 2008 to 8.1% in 2017 (P < .001). AF was associated with adverse clinical outcomes, such as in-hospital mortality, congestive heart failure, pulmonary circulation disorders, renal failure, fluid and electrolyte disorders, cardiogenic shock, higher total cost, and longer length of hospital stay. Conclusions: The prevalence of AF among inpatients with PC increased from 2008 to 2017.AF was associated with poor prognosis and higher health resource utilization. Better management strategies for patients with comorbid PC and AF, particularly in older individuals, are required.